EFFECT OF SEASON ON SOME REPRODUCTIVE BEHAVIOURAL CHARACTERISTICS OF AWASSI SHEEP UNDER SUB-TROPICAL MEDITERRANEAN CLIMATIC CONDITIONS - S. Gül (Journal of Animal and Plant Sciences, 2012)
The present study was planned to investigate some reproductive behavioural characteristics in six fat-tailed male, single born Awassi rams.  Mating behaviour characteristics were recorded for every two months starting from June for a year. Each ram was arranged to mate with 2 different ewes in similar live weight. The ewes were synchronised for oestrus using progesterone sponges and PMSG. The ewes were checked for oestrus at least three times a day, and were considered to be in heat when they stood for mounting by a teaser. After that, ewe in heat was transferred to another individual unit (5 m x 10 m) for mating with the experimental ram. Each ram was allowed to mate maximum 2 ewes during each joining. The observed behavioural characteristics were sniffing, Flehmen, licking, low-strech, scraping to earth, striking by the front feet to the earth surface, striking by the front feet to the shoulder of ewe. It was concluded that the sexual behavioural characteristics of Awassi sheep differed in different seasons.
Keywords: Awassi sheep; seasonal reproductive behaviour characteristics